L’indisponibilità del diritto all’integrità fisica della persona umana in ambito sportivo e i limiti al rischio consentito - Maria Cimmino (Universidad Hemisferios, 2016)
Nowadays, people engage in fun and exciting activities, which are risky, knowing that they might be injured, or incur some type of property damage. Sports and physical activities could also be dangerous for people’s health and safety, because it often has inherent risks that cannot be eliminated without destroying the very essence of the activity. According to the doctrine of the assumption of risk, a participant in a sporting activity accepts its normal and reasonable risks and ordinary blows and collisions incidental that happen during the match, but the athlete does not accept the abnormal incidents. Sport is also one of the necessities of communities, because it can improve common and individual wellness and encourage the diffusion of the value in the modern society. How and when should the assumption of risk be applied in the sport? This paper would like to analyze the relationship between sport right and personal injury; the aim is to verify how the Italian legal system ensure the promotion of the sport by protecting the safety and the physical integrity of the human person, as fundamental right, in the light of the doctrine of the assumed risk.